Life satisfaction, contract farming and property rights: Evidence from Ghana - Susanne Väth; Simone Gobien (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
Large-scale land acquisition has increased dramatically in recent years. The question whether land deals can benefit both the local population and the investor is therefore high on the international agenda. Contract farming is discussed as a possible solution but studies identifying the causal effects are rare. Using data from a quasi-natural experiment in contract allocation, we compare the subjective well-being of outgrowers and independent farmers in the sphere of the biggest palm oil producer in Ghana. We identify a positive causal effect of the outgrower scheme which increases subjective well-being by 1.5 points on a scale of 0 to 10. We find a substitutive relationship between having an outgrower contract and having property rights, and thus we argue that by increasing security a contract increases well-being, as secure rights to land matter substantially for the overall life satisfaction of non-contract but not of contract farmers.
Keywords: D60; I31; Q13; 330; contract farming; property rights; quasi-natural experiment; subjective well-being; large-scale land acquisition